Utilization Of Batik Cultural Arts for Human Resources Development - Priyanto, Priyanto (Journal of Indonesian Tourism and Policy Studies, 2024)
Abstract. Batik art has been confirmed as cultural intangible from Indonesia by UNESCO. The art of batik contains many values that are characteristic of the Indonesian people because batik is an identity, explanation of social strata, cultural language, human spirituality, technological discoveries, and the journey of an Indonesian civilization. In its journey, the existence of batik art has been quite affected by the onslaught of foreign culture flowing in the swift globalization. The Indonesian people should have taken a stand to maintain and preserve the art and culture of batik. This encourages artists to take part in the preservation and development of batik art. One of them is by utilizing the art of batik by exploring the leadership values that exist in the art of batik to increase the competence of human resources. This study aims to explore the preservation and development of batik art and examine the values of leadership in batik art. This study uses a qualitative methodology. The results of the research show that batik art can be used as leadership training material as well as for preservation and in batik art there are leadership values that can be implemented in everyday life. This paper provides a discussion on the art of batik for leadership material for preservation and exploring the values of leadership in the art and culture of batik. Keywords: Leadership values, batik arts and culture